Investigating Teachers’ Integration of Technology in Automotive: A Case in Technical Schools - Morudu, Koketso (Research in Social Sciences and Technology, 2025)
The study aimed to examine how teachers in technical schools in automotive classrooms integrate technology, employing a case study research approach. The Technological Pedagogical Content Knowledge (TPACK) model coined by Mishra & Koehler (2006) was used to underpin the study as a framework. It emerges as a useful construct for researchers working to understand technology integration in learning and teaching. We collected data by conducting face-to-face interviews with automotive teachers and making observations during the study period. Interviews were thematically analysed through verbatim quotes, and observations were analysed descriptively. Existing literature provides various factors that contribute to the difficulties of teaching and learning automotive. The aim and purpose of this study were to examine and explore automotive teachers’ knowledge in terms of how they integrate technology in automotive. The participants who were regarded as knowledgeable and experienced in automotive were selected using a convenient sampling method. The study made use of a case study approach. The data collected was thematically analysed and presented using categories such as teachers with experience showing enhanced technology integration, teachers engaging in active learning, teachers showing positive attitudes towards the integration of technology, and teachers believing in blending classroom and workshop teaching styles. The teachers emphasised access to the workshops, machinery, and knowing how to use them. The findings suggest that innovative strategies, including but not limited to being proactive, improvising, and seeking assistance, can be used to integrate technologies. The study reveals that the teachers attempted to use various innovative strategies for integrating educational technologies into their instructional methods. Teachers were in pursuit of integrating content, pedagogy, and technological knowledge for successful teaching. Automotive teachers need to be TPACK specialists to successfully integrate pedagogy, content, and technology into their teaching to maximise the process of knowledge construction. The study suggests that technical schools offering automotive courses, the Department of Education, and other key stakeholders should implement innovative strategies to facilitate the complete integration of technology. Furthermore, it recommends that teachers receive continuous training in using innovative technology. The study recommends that technical schools offering automotive, the Department of Education, and other key stakeholders implement innovative strategies to help in the complete integration of technology. Furthermore, it recommends that there should be continuous training in the use of innovative technology for teachers.